Core Entrepreneurial Competencies for Local Content Curriculum - Djubaedi, Dedi; Rohadi, Tedi; Kodama, Yayoi (International Journal of Educational Qualitative Quantitative Research, 2023)
One of the severe problems facing the world-wide is a large number of unemployed, both high school graduates who do not continue their tertiary education and university graduates. The curriculum requires competency content to prepare graduates who are ready to work. One alternative is implementing an entrepreneurship curriculum so that graduates can decide on a career after graduation. This study aims to identify what core competencies are needed to start/start-up, manage, and develop the entrepreneurship local content curriculum for Islamic High Schools. This research method is a descriptive qualitative survey technique. The survey results were discussed through Focus Group Discussion with the participants, who were curriculum and entrepreneur experts from IAIN Syekh Nurjati Cirebon Indonesia and Kitakyushu University Japan. The result shows that the core and basic competencies consist of the knowledge, skills, and attitudes entrepreneurs must possess. The six core entrepreneurial competencies for local content curriculum are 1) Identifying business opportunities and exploiting businesses; 2) Implementing managerial activities; 3) Implementing human resource management; 4) Implementing commercial and marketing activities; 5) Implementing financial management; 6) Actualizing attitudes and behavior. This research contributes to providing knowledge to educational stakeholders to improve the quality of education by increasing its relevance in graduate employment.